An exchanger-like protein underlies the large Mg(2+) current in Paramecium - Haynes, W. John (National Academy of Sciences, 2002)
There are very few molecules known to transport Mg(2+) in eukaryotes. The membrane of Paramecium tetraurelia passes a large Mg(2+)-selective current and exhibits a corresponding backward swimming behavior. Both are missing in a group of mutants called eccentric. By sorting an indexed WT genomic library through microinjection into the macronucleus, we have isolated a DNA fragment that complements the eccentric mutations. The Mg(2+) currents and behavior are restored fully in the transformed cells. Surprisingly, the conceptually translated protein is not homologous to any known ion channel but instead has some similarity to K(+)-dependent Na(+)/Ca(2+) exchangers. Exchangers are either electrically silent or only pass very small and slow currents compared with ion-channel currents. In light of recent ion-channel crystal structures and considering the need to have narrow ion-selective filters, we speculate on how an exchanger might evolve to show channel-like activities in special circumstances. The significance of finding the molecular basis of a Mg(2+)-specific pathway is also discussed.